Il sepolcro di Orfeo. Appunti per l’identificazione di un rituale funerario orfico-bacchico - D’Orlando, Dario (O T I V M, 2017)
For the orphic believer death is only a necessary passage to a better afterlife. For this reason the moment of the burial could have been an important moment in the life of the initiate. In this work the author tries to analyze if the tombs with the so-called orphic leaves are reliable with orphic beliefs. The choice of the funerary rite in fact is seen as an important aspect for many religions in the ancient times. In order to put together the elements acquired from the archaeological contexts known and what is possible to read from classical literature, this work is aimed at the reconstruction of the burial preferences – if they exist –, of the orphic believers. The unusual choice of inhumation in areas where is not common, like Pelinna in Thessaly, is a curious element that has to be explained.